Pengaruh Penerapan Akuntansi Manajemen Lingkungan Terhadap Kinerja Lingkungan Yang Dipengaruhi Oleh Faktor Kepemimpinan, Budaya, Inovasi Dan Kemampuan Pada Pabrik Tekstil - Marcella Trianita Abur; Hwihanus Hwihanus (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Environmental Management Accounting is . This research aims to examine the influence of environmental management accounting on environmental performance. This research, in testing the Y value, uses several indicators including innovation, ability, culture and leadership. The innovation referred to is process innovation within the company, the capability referred to is the company's ability to process and produce, the culture referred to is the implementation of the vision and mission implemented by the company and the leadership referred to is the impact on the surrounding environment. The samples used were 5 textile companies listed on the Indonesian Stock Exchange. The research method used is with the help of Smart PLS Software. The significance of parameters is tested by comparing the calculated t value with t calculated > t table at a confidence level of 0.005, meaning that there is a significant influence. Hypothesis testing to answer temporary answers using Pathcoefficients significance. The research results show that five indicators have a positive influence on environmental performance prospectors with a statistical value of 0.282.